Intention to Visit Sustainable Tourism Destination After Covid 19 Pandemic - Ekasari, Ayu; Pratomo, Luki Adiati; Rahayu, Fatik; Bangun, Cicilia; Hidayat, Darra Pradita (Universitas Trisakti, 2023)
This paper aims to investigate the antecedents of environmental attitude and its influence on intention to visit sustainable tourism destination, which is moderated by individual green value. Purposive sampling method was used to collect the data from 370 respondents. The data was analysed using structural equation model. Out of the four antecedents, environmental identity and enjoyment of nature positively influence environmental attitude that leads to intention to visit. Results also showed that individual green value moderates the influence of environmental attitude on intention to visit sustainable tourism destination. This research suggests sustainable tourism marketers to create message that form positive environmental attitude. This study offers a conceptual model that focusing on environmental attitude as a key variable that is widely proven to be the best predictor of intention.